MEDIA KARTU KEMUDI PINTAR (KKP) BERBASIS GRAFIS UNTUK PENGUASAAN KOSAKATA NOMINA SINGULAR DAN PLURAL BAHASA JERMAN PESERTA DIDIK KELAS XI SMA NEGERI 12 SURABAYA - PUTRI HEMI, ROSIANA (LATERNE, 2016)
vocabulary is a very important component in learning German language. Though vocabulary, student can apply the four language skills of reading, writing, speaking and listening. To be able to mastery vocabulary necessary to have media that facilitate mastery vocabulary in German language. Based on questionnaire data showed that 75,66% of student have difficuly in learning vocabulary, especially singular and plural nouns. This study describes the development steps media and instructions for use. This research method is descriptive qualitative. The result of this research ia a product for vocabulary singular and plural nouns named Kartu Kemudi Pintar (KKP) based on graphic. Kartu Kemudi Pintar (KKP) based graphic consists of square side 31 cm and two cricles with a diameter 23,5 cm. Made from Paper Aert 260g/m2. In der middle of Kartu Kemudi Pintar (KKP) give doff that can be played like a steering wheel. On the side of square divided intto 18 parts, and then add the picture and name of the nouns Elektric and Non-Electric accordance Object in School. The square is blue and the circles is red. Kartu Kemudi Pintar (KKP) based graphic is expected to be used by teachers in teaching vocabulary in German language effectively and efficiency.Keyword : Media, Kartu Kemudi Pintar (KKP), Vocabulary